2013
DOI: 10.1007/s00586-013-3035-7
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray assessment of the effect of pedicle screw on vertebra and spinal canal growth in children before the age of 7 years

Abstract: Purpose To determine the reliability of pedicle screws placed in children younger than 7 years of age, and to evaluate the effect of pedicle screw insertion on further growth of the vertebra and spinal canal. Methods A retrospective study of 35 consecutive patients through Jan 2003-Dec 2010 for congenital scoliosis in \7 years children was performed at one spine center. Patients undergoing pedicle screw instrumentation of at least two levels, which had been followed-up for at least 24 months were included. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The findings of the current study are complementary to the previous studies [7][8][9][10][11] in terms of the instrumentation's effect on the spinal canal in pediatric spine. By measuring the same vertebrae on the CT scans postoperatively and at the last follow-up, we have observed that pedicle screws insertion in children younger than 5 years of age do not alter the growth of the spinal canal.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The findings of the current study are complementary to the previous studies [7][8][9][10][11] in terms of the instrumentation's effect on the spinal canal in pediatric spine. By measuring the same vertebrae on the CT scans postoperatively and at the last follow-up, we have observed that pedicle screws insertion in children younger than 5 years of age do not alter the growth of the spinal canal.…”
Section: Discussionsupporting
confidence: 84%
“…Although the effect of pedicle screws on the development of the growing spine remains controversial, the consensus held is that the fusion region in the pediatric spine should include as few vertebrae as possible to minimize the impact on the longitudinal growth of the immature spine [8,11]. However, shortening of the fixation region, accompanied by the tiny pedicles and the thin cortical vertebral shells in pediatric patients, most likely leads to weak fixation strength and perhaps increases the likelihood of pedicle screw pull-out [12,13], correction loss [14], crankshaft phenomenon [15] and quadrilateral shift [16].…”
Section: Introductionmentioning
confidence: 99%
“…There are very few clinical and radiological studies which evaluated the effect of pedicle screw instrumentation before age 5 years, on the growth of vertebra and spinal canal development [1][2][3]. Ruf et al [2] and Xue et al [1] in their series evaluated immature spinal growth of their patients mostly with plain radiographs.…”
Section: Introductionmentioning
confidence: 98%
“…Ruf et al [2] and Xue et al [1] in their series evaluated immature spinal growth of their patients mostly with plain radiographs. Olgun et al [3] used preoperative computerized tomography (CT) scans or magnetic resonance imaging (MRI) and compared postoperative CT scans to evaluate the effect of pedicle screw instrumentation on vertebral body and spinal canal growth in a group of patient with minimum 2 years follow-up.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation